LEGAL PROTECTION FOR CONSUMERS FOR ELECTRONIC GOODS THAT DO NOT HAVE SNI (INDONESIAN NATIONAL STANDARD) - Dani fadhlurrahman; Fauzul Aliwarman (JOSAR (Journal of Students Academic Research), 2023)
The purpose of writing this article is to examine legal protection for consumers for electronic goods that do not have SNI (Indonesian National Standard), and understand consumer legal remedies for resolving disputes over losses caused by electronic goods that do not have SNI (Indonesian National Standard). The research method used is a normative legal research method through an approach to legislation. The results of this study show that the legal protection for consumers of electronic goods that do not have SNI (Indonesian National Standards) is protected not only by law no. 8 of 1999 concerning Consumer Protection Article 8 paragraph (1) letter a, but is also regulated by Law No. 20 of 2014 concerning Standardization and Conformity Assessment and is also regulated by the Regulation of the Minister of Industry of the Republic of Indonesia Number 15 of 2018 concerning the Enforcement of Indonesian National Standards (SNI). In Mandatory Audio Video and Similar Electronic Products. Consumer legal efforts in resolving disputes over losses caused by electronic goods that are not SNI (Indonesian National Standard) based on Law no. 8 of 1999 concerning Consumer Protection are regulated in Article 45 paragraph (1). Consumers can sue business actors through an institution tasked with resolving disputes between consumers and business actors/consumers can sue through a court within the scope of the general court.